Free trade in the Americas : interim report (Senate of Canada [Ottawa]CA, 1995)
Summarises the economic difficulties in which Latin America found itself in the 1980s. Examines the size, composition and potential implications of capital inflows to Latin America. Provides a progress report on the major integration efforts underway within the hemisphere. Looks at the plan to create a Free Trade Area of the Americas which came out of the Summit of the Americas and examines Chile's proposed accession to NAFTA. Outlines Canadian trade policy toward the Caribbean and examines the origins and implications of the 1994-1995 Mexican currency crisis.
DC